Emotional Valence Affects Word Retrieval During Verb Fluency Tasks in Alzheimer’s Dementia - Paek, Eun Jin (Frontiers in Psychology, 2021)
Individuals with amnestic Alzheimer’s disease (AD) often demonstrate preserved emotional processing skills despite the neurodegenerative disease that affects their limbic system. Emotional valence encompasses the encoding and retrieval of memory and it also affects word retrieval in heathy populations, but it remains unclear whether these effects are preserved in individuals with amnestic AD. Previous studies used a variety of encoding procedures and different retrieval methods that resulted in mixed findings. Therefore, the purpose of the current study is to investigate whether emotional enhancement of memory effects are observed in an experimental condition where the memory encoding process is not required, namely verb (action) fluency tasks. 17 participants who were cognitively healthy older adults (CHOA) and 15 participants with amnestic AD were asked to complete verb fluency tasks and the relative degree of emotional valence observed in their responses was compared between the two groups. A neuropsychological test battery was administered to determine the participants’ cognitive and linguistic profiles and correlational analyses were conducted to delineate relationships between emotional valence, verbal memory, and learning abilities. The results indicated that the participants with amnestic AD produced words with higher emotional valence (i.e., more pleasant words) compared to CHOA during action fluency testing. In addition, the degree of emotional valence in the words was negatively correlated with verbal memory and learning skills, showing that those with poorer memory skills tend to retrieve words with higher emotional valence. The findings are consistent with those previous studies that stressed that individuals with AD have preserved emotional enhancement of memory effects and may benefit from them for retrieval of information, which may offer some insight to the development of novel rehabilitative strategies for this population.